Soda lignin as a sustainable photosensitive component for conventional and controlled radical photopolymerization - Min Wang; Xiongfei Luo; Qunying Wang; Veronika Strehmel; Zhijun Chen; Shujun Li; Bernd Strehmel (Communications Chemistry)
Abstract Valorization of waste for chemical processes addresses a challenging task for the society. Soda lignin (AL) available in the pulp industry operated in a photocatalytic cycle CuX2/L (X: Br, Cl; L: Me6TREN: Tris[2-(dimethylamino)ethyl]amine) and to initiate radical photopolymerization of methyl methacrylate (MMA) with α-bromophenylacetate (EBPA) by exposure at 420 nm. This resulted in poly(methyl methacrylate) (PMMA) exhibiting a dispersity <1.3 with CuX2/L loading of ≲52 ppm. Deactivator reduction increased dispersity. MMA, styrene, and benzyl methacrylate successfully served as monomers for chain extension and block copolymerization experiments. This worked with CuX2/L ≥ 6.5 ppm, although conventional radical polymerization additionally competed. Adding of sodium pyruvate enabled radical photopolymerization under air. Modification of lignin with an aryl sulfonate group resulted in a one-component photoinitiator. It successfully initiated radical photopolymerization of a monomer mixture of (hydroxyethyl)methacrylate (HEMA) and urethane dimethacrylate (UDMA). Scale-up experiments approved practicability of photo-ATRP.